Factors Affecting the Decision to Participate in Cash Waqf Linked Blue Sukuk (CWLBS) - Lu’liyatul Mutmainah; Yan Putra Timur; Muhammad Hanif Ibrahim; Nur Arifah (Badan Wakaf Indonesia, 2026)
The establishment of Cash Waqf Linked Sukuk (CWLS) by the Indonesian government marked the beginning of the integration of social and commercial Islamic finance. The purpose of this study is to examine the factors that influence the public to participate in proposed financial innovations with the Cash Waqf Linked Blue Sukuk (CWLBS) scheme. The Technology of Acceptance Model (TAM) technique was adapted for this study with some additional variables. An online questionnaire was used in this study with 230 respondents and Partial Least Square-Structural Equation Modeling (PLS-SEM) was used to examine the data. This study provides examples of the step-by-step robustness phases in split-sample, effect size, and partial least square approach. This study suggests that behavioral intention (BI) in contributing to CWLBS is significantly influenced by environmental awareness (EA), trust (TR), and religiosity (RLG). However, Perceived ease of use (PEOU) and perceived usefulness (PU) has no significant influence to BI. Additionally, trust was successful in mediating the PEOU and PU relationship with BI. Furthermore, religiosity was successful in moderating PU on BI. However, it was not successful in moderating PEOU on BI. This result emphasizes that financial technology helps waqf contributors gain access and take part in this program if it is supported by trust to the waqf institution. Islamic financial innovation with environmental concerns still needs to be elaborated to give a more significant impact. This research is one of the initial studies to analyze the factors influencing people to participate in the integration of cash waqf and Blue Sukuk as innovative financing that supports Sustainable Development Goals Number 14 that is life below water.